The Influence Of Social Capital, Family Resources And Work Ethic On Economic Resilience And Family Welfare In North Central Timor District - et. al., Emanuel Be, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research objective was to analyze the influence of social capital and family resources in improving work ethic and family economic resilience which can be felt through family welfare. The sampling technique uses non-probability sampling and data collection methods through non-behavioral observation, structured interviews and in-depth interviews. The primary data source used questionnaires and interviews and used a sample of 205 heads of underprivileged families. Data analysis techniques with descriptive statistics and structural equation modeling using Partial Least Square. The results showed that: social capital and family resources had a significant effect on work ethic. Social capital and work ethic have a significant effect on economic resilience, while family resources do not have a significant effect on economic resilience. But overall, social capital, family resources, work ethic and economic resilience have a significant influence on family welfare. The positive influence of social capital and family resources through work ethic on economic resilience. Economic resilience mediates the effects of social capital, family resources and work ethic on family welfare.